BIBLIOMETRIC ANALYSIS OF THE DIFFERENCES AND RELATIONSHIPS BETWEEN RELIGIOUS TOURISM AND SPIRITUAL TOURISM - Agustia Dzikir Maulani; Sapto Supriyanto; Apri Kuntariningsih (International Journal of Social Science, Educational, Economics, Agriculture Research and Technology (IJSET), 2026)
This study aims to analyze the research landscape on religious tourism and spiritual tourism within the context of destination management using a bibliometric approach. Data were retrieved from the Scopus database with the keywords “destination management” AND (“spiritual tourism” OR “religious tourism”). After filtering by language, publication stage, and year, a total of 210 documents were analyzed using VOSviewer software. The co-occurrence analysis with a minimum threshold of three occurrences identified 49 keywords that met the criteria and formed four main thematic clusters. The mapping results reveal that religious tourism is primarily examined from the perspectives of destination management, tourism economics, and cultural heritage preservation. In contrast, spiritual tourism focuses more on tourists' psychological and personal experiences. Both themes intersect strongly through issues such as sustainability, cultural heritage, and service quality. These findings highlight the need for a multidisciplinary approach to developing tourism destinations that balance economic and managerial goals with spiritual and social values. Future research is recommended to strengthen the integration between spiritual and managerial dimensions and enhance cross-national collaboration to broaden perspectives in the study of spiritual and religious tourism.